Gender and natural resource governance indicators: a need to assess and address 'sensitive and taboo' topics - Colfer, C.J.P.; Achdiawan, R.; Adnan, H.; Erni Yuliani, L.; Balang; LepMil (Informa UK Limited, 2013)
Gender and governance or management are topics that have been inadequately addressed by researchers, with resulting very slow progress towards gender equity globally. A collaborative landscape management project in South and Southeast Sulawesi (Indonesia) has been trying to strengthen women's voices in local management and governance and to encourage more equitable benefit distribution throughout the landscape. The need for a simple assessment of the project's success presented an opportunity for us to develop a set of indicators that we believe can be adapted and used more widely. Our indicators, presented below, differ from other indicator sets available, most fundamentally in their foci on (1) gender and governance/forest management, (2) a combination of production and other more sensitive issues central to women's lives, and (3) intra-household decision-making.